Autologous retinal graft for the management of large macular holes associated with retinal detachment. Issue 1 (31st December 2023) - Zgolli, Hsouna; Elzarrug, Hamad K H; Abdelhedi, Chiraz; Mabrouk, Sonya; Fekih, Olfa; Malek, Ines; Zghal, Imen; Nacef, Leila
ABSTRACT: To present the efficacy of autologous neurosensory retinal transplantation in macular holes surgery with rhegmatogenous retinal detachment. Eleven eyes of 11 patients with rhegmatogenous retinal detachment associated to a large macular hole were enrolled between January 2019 and January 2021 in the Department A of the Hedi Rais Institute of Ophthalmology (Tunis, Tunisia). All patients underwent a 23 G pars plana vitrectomy. An autologous neurosensory retinal patch was placed inside the macular hole. Long-acting silicone tamponade was carried out. Clinical features of the macular area, best-corrected visual acuity (BCVA), fundus examination, and SD-OCT were recorded before surgery, at 1- and 3-month follow-up after surgery. The mean age of our population was 56.6 ± 10.33 years old, ranged from 45 to 76 years old. Final retinal reattachment was achieved clinically in all eyes. The Spectral domain-Optical Coherence Tomography (SD-OCT) follow-up showed the macular hole closure. The retinal patch was demonstrated by OCT at each control. BCVA improved from 1.52 ± 0.23 Logarithm of the Minimum Angle of Resolution (LogMAR) to 0.89 ± 0.16 LogMAR 3 months after surgery ( p = 0.014). No adverse events were registered during the study. Autologous neurosensory retinal transplantation has been efficient to treat macular hole associated to rhegmatogenous retinal detachment. Further multicentric studies with a large number of patients are needed to establish the results of this technique in complex cases.